MN(II) ION ADSORPTION USING FLOATING ?-CARRAGEENAN BEADS - Izzah, Rasya
The rapid economic growth has an impact on increasing industrial activity which produces heavy metal waste in the environment, one of which is the heavy metal ion Mn. This can have a negative impact on human health if the levels of Mn(II) found in the environment exceed the limits. Polysaccharides are biopolymers that can be used as adsorbent bases to remove pollutants in water such as Mn(II) ions because they have a high surface area and porosity. In this study, the adsorbent of floating ?-carrageenan beads was used to adsorb Mn(II) ions present in water. Floating beads will facilitate the process of separating the adsorbent after contact. The preparation of floating ?-carrageenan beads was carried out by adding CaCO3 compounds with the mass ratio of 4:1 for ?-carrageenan:CaCO3. Characterization of floating ?-carrageenan beads was carried out by increasing the degree of swelling and floating time, as well as characterization using Fourier Transform Infrared (FTIR) instruments to prove the success of synthesis and the adequacy of the functional groups. The floating ?-carrageenan beads had a swelling degree of 525,64% with a float time of 5 hours and the FTIR characterization showed a fingerprint peak of ?-carrageenan. The adsorption capacity of floating ?-carrageenan beads was determined by measuring the remaining Mn(II) ions after contact using an Atomic Absorption Spectroscopy (AAS) instrument. he adsorption study gave the maximum adsorption capacity of Mn(II) ions using floating ?-carrageenan beads of 18,19 mg g?1. Adsorption of Mn(II) ions using floating ?-carrageenan beads optimally at pH 5, adsorbent mass of 0,1 gram, and contact time of 90 minutes. Attempting to play the effect of initial concentration and temperature on the adsorption of Mn(II) ions by floating ?- carrageenan beads. Adsorption of Mn(II) ions using floating ?-carrageenan beads followed the Langmuir isotherm adsorption model with an R2 value of 0,9949, a pseudo second order adsorption kinetics model with an R2 value of 0,9965, and thermodynamics of Mn(II) adsorption using floating ?-carrageenan beads showed spontaneous and exothermic adsorption as indicated by the ?G values of ?165.59 (303 K) respectively, ?168.48 (313 K), ?171.37 (323 K) kJ.mol?1 and ?H and ?S values of ?78.07 kJ.mol?1 and 288.85 J.K?1.mol?1.